Extraradical hyphae exhibit more plastic nutrient-acquisition strategies than roots under nitrogen enrichment in ectomycorrhiza-dominated forests - Zhu, Xiaomin (Global change biology, 2023)
© 2023 John Wiley & Sons Ltd.